Intervensi Pencegahan Bullying pada Anak Berbasis Sekolah - Ike Sintia Suci; Gusgus Ghraha Ramdhanie; Henny Suzana Mediani (Jurnal Keperawatan Silampari, 2021)
This study aims to review or review the literature related to school-based bullying prevention interventions in children. Methods This research was conducted using a literature review method. Articles were identified using an electronic database, including PubMed, Science Direct, DOAJ, and ERIC, using keywords to answer research questions formulated using the PICOS method. The results showed that five articles were selected from 40 reports that matched the eligibility criteria. Based on the analysis results, the 5 articles had a significant effect on school-based bullying prevention interventions, such as including prevention programs in the curriculum or school extracurricular activities by involving various stakeholders. In conclusion, school-based intervention proved to be effective as an intervention to prevent bullying. Keywords: Bullying, Intervention, Prevention, School